Khilafah Vis A Vis Demokrasi: Menguak Sistem Pemerintahan Negara Plural yang Mayoritas Penduduknya Muslim (POLITEA, 2021)
The debate about the democratic system in Islamic State has not ended. This is because there are Muslim groups that are inclusive in nature who do not want to accept all teachings or conceptions that come from the West, especially regarding the democratic system. This group is known as an Islamist group that applies the principles of formalization of sharia. However, in another spectrum there are Muslim groups who openly accept the democratic system originating from the West. Because for them the democratic and Islamic System are mutually compatible, there is no conflict. By using the library research method, this research wants to find answers to the confusion regarding the existing government system in an Islamic country or a country with a Muslim majority population. Because this government system is important in not changing the Islamic state. Changes that can compete with other countries in the West, which until now have not been able to stand side by side with Islamic countries regarding a good and well-ordered political system.